Oracle database 12c new features - Freeman, Robert G. 1965- (McGraw-Hill Education, 2014)
Maximize the New and Improved Features of Oracle Database 12c Written by Master Principle Database Expert, Oracle, and Oracle ACE Robert G. Freeman, this Oracle Press guide describes the myriad new and enhanced capabilities available in the latest Oracle Database release. Inside, you'll find everything you need to know to get up and running quickly on Oracle Database 12c. Supported by running commentary from world-renowned Oracle expert Tom Kyte, and with additional contributions by Oracle experts Eric Yen and Scott Black, Oracle Database 12c New Features offers detailed coverage of: *Installing Oracle Database 12c *Architectural changes, such as Oracle Multitenant *The most current information on upgrading and migrating to Oracle Database 12c *The pre-upgrade information tool and parallel processing for database upgrades *Oracle Real Application Clusters new features, such as Oracle Flex Cluster, Oracle Flex Automatic Storage Management, and Oracle Automatic Storage Management Cluster File System *Oracle RMAN enhancements, including cross-platform backup and recovery *Oracle Data Guard improvements, such as Fast Sync, and Oracle Active Data Guard new features, such as Far Sync *SQL, PL/SQL, DML, and DDL new features *Improvements to partitioning manageability, performance, and availability *Advanced business intelligence and data warehousing capabilities *Security enhancements, including privileges analysis, data redaction, and new administrative-level privileges *Manageability, performance, and optimization improvements. --
Includes index. - Print version record
Keywords: Oracle (Computer file); Data warehousing; Database management; Entrepôts de données (Informatique); Bases de données; Gestion; Llibres electrònics